Distalization and Medialization of Tibial Tuberosity for the Treatment of Potential Patellar Instability with Patella Alta - Enea, Davide; Canè, Pier Paolo; Fravisini, Marco; Gigante, Antonio; Dei Giudici, Luca (Joints, 2018)
Purpose The aim of the study was to test the distalization and medialization of the tibial tuberosity (DMTT) for the treatment of patellar instability associated with patella alta, focusing on residual instability and pain.Methods Twenty-four consecutive patients (26 knees) suffering from patellofemoral instability and patella alta were treated by DMTT. Two groups were identified, which differed for documented history of frank patella dislocation. The groups were named objective patellar instability (OPI) (history of dislocation) and potential patella instability (PPI) (no dislocation). Outcome was measured with visual analogue scale (VAS), Kujala score, and Tegner score. Comparison between groups was performed using Student's t-test, Wilcoxon rank score, and Fisher's exact test (significance at p < 0.05).Results At 50 ± 18 and 41 ± 18 months of follow-up, respectively, both PPI and OPI groups obtained a significant pain reduction and functional improvement. The PPI group showed a significant decrease of the subjective instability. No procedure-related complications were reported.Conclusion This study suggests that DMTT is a viable option for PPI patients with patella alta. The outcome was comparable between PPI and OPI cases; however, decrease in subjective instability was significantly greater in PPI patients.Level of Evidence Level III, retrospective comparative study.
Keywords: patellar instability; distalization; medialization; patella alta; tibial tuberosity